2019
DOI: 10.3126/jnprossoc.v2i1.26809
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Tooth Morphology among the Dentists of Kathmandu

Abstract: Background: Dental anatomy is taught as a basic dental subject in dental schools of Nepal. The knowledge has immense use in clinical practice in dentistry. However, few people feel that it has no use and should be removed from the dental curriculum. The objective of the study was to analyze the knowledge, attitude and practice of tooth morphology among dental practitioners in Kathmandu. Materials and Methods: A cross-sectional study was undertaken among the dental practitioners in Kathmandu using a self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The results of the present study are also similar to the results of a study by Singh et al [7] A similar study conducted among dental practitioners has revealed that more than 90% of the respondents agreed that an understanding of tooth morphology has helped them in clinical practice. [8] In a study by Nayak et al, 65% of the respondents believed that tooth carving helped them in their clinical skill and that too in the conservative dental practice. [9] Some authors feel that the carving of the root is unnecessary and more important needs to be given to the crown n portion of the tooth.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present study are also similar to the results of a study by Singh et al [7] A similar study conducted among dental practitioners has revealed that more than 90% of the respondents agreed that an understanding of tooth morphology has helped them in clinical practice. [8] In a study by Nayak et al, 65% of the respondents believed that tooth carving helped them in their clinical skill and that too in the conservative dental practice. [9] Some authors feel that the carving of the root is unnecessary and more important needs to be given to the crown n portion of the tooth.…”
Section: Resultsmentioning
confidence: 99%